Report on the best means of facilitating land transfer, by means of local registry - Donnell, Robert (Statistical and Social Inquiry Society of Ireland, 1874)
The question of the comparative merits of large and small farms has been one of the best debated in Political Economy. The controversy cannot be said to be yet terminated. But some portions of the field have become neutral ground. The advocates of large farms admit that under certain conditions their favourite system is physically impossible; and that social circumstances may sometimes render its introduction a matter of far-off futurity. And I think the advocates of small farms have, from a very wide induction, established beyond dispute one position at all events, that if the system of small farms is to exist, peasant proprietorship is economically preferable to any system of limited interest in the cultivator.
Read before the Society, 16 December 1873
Keywords: Land reform; Ninteenth century Ireland; Land transfer; 314.15